AN ANALYSIS OF CLASSROOM STUDENTSâ MISBEHAVIORS IN MECHANICAL ENGINEERING DEPARTMENT CLASS OF GRADE XI IN SMK NEGERI 3 SINGARAJA - Wedhanti, N.K; Sasih, L.L. (Universitas Pendidikan Ganesha, 2017)
This descriptive qualitative research was aimed at finding out the kinds of studentsâ misbehavior in the classroom of Mechanical Engineering Department of grade 11 in SMK Negeri 3 Singaraja, knowing the studentsâ reasons for doing misbehaviors in the classroom, and also the aim at knowing the teacherâs responses towards the studentsâ misbehaviors happened in the classroom. The subject of this research was all students in the classroom of Mechanical Engineering Department of grade11 and their English teacher. Observation and interview were the techniques used to collect the data of this research. Descriptive qualitative techniques were then used to analyze the data that was gathered. The result of this research showed that there were ten kinds of studentsâ misbehavior happened in the classroom of Mechanical Engineering Department grade 11 in SMK Negeri 3 Singaraja. Those misbehaviors were inattention, apathy, needless talk, moving about the room, annoying others, disruption, lying, cheating, aggression and fighting, and also defiance of authority. Six of those misbehaviors happened consistently and four of those misbehaviors happened inconsistently in the classroom. There were found six studentsâ reasons for doing those ten kinds of misbehavior in the classroom. After that, there were found five teacherâs responses towards misbehaviors done by the students in the classroom of Mechanical Engineering Department of grade 11 in SMK Negeri 3 Singaraja.